AWARENESS TO ACTION: GLOBAL CITIZENSHIP EDUCATION IN A LOCAL HIGHER EDUCATION CONTEXT (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2025)
This study investigates the awareness and integration of Global Citizenship Education (GCED) principles within the community of the City College of Calamba (CCC). Grounded in UNESCO’s GCED framework and the UN Sustainable Development Goal (SDG) 4.7, the research addresses a critical gap in Philippine higher education literature by examining local institutional practices. A quantitative descriptive survey design was employed, utilizing a UNESCO-adapted instrument administered to 103 teaching and non-teaching staff. Non-parametric tests revealed no statistically significant differences in awareness levels of cognitive, socio-emotional, and behavioral dimensions across gender. Findings show high levels of awareness but weaker integration into teaching practices and professional services. The study highlights both opportunities and challenges in operationalizing a whole-school approach to GCED. Contributions include practical recommendations for curriculum enhancement, staff training, and policy reforms that can inform not only CCC but also other similar higher education institutions in the Asia-Pacific region.
Keywords: Global Citizenship Education; Awareness; Integration; Gender Differences; Higher Education; Philippines